Reduksi Peak to Average Power Ratio (PAPR) Menggunakan Teknik Clipping - Muhammad Fitrah Sugita; Risanuri Hidayat; Sri Suning Kusumawardani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
Frequency Division Multiplexing (OFDM) has aweakness that lies at the high power variation. Power variationis stated in peak-to-avarage power ratio (PAPR). PAPR is the ratio between the maximum and average power of OFDM signal at the certain time frame. High PAPR value will result in nonlinear distortion when operating on non linear devices such as high power amplifier (HPA). Therefore, it is necessary to find way to reduce PAPR value. In this paper, we used PAPR reduction simulation using clipping techniques. PAPR reduction is done by clipping of the output signal of IFFT block which has a PAPR value exceeds the clipping level clipping value is determined by the ratio of the test using the clipping ratio is 0.8 and 1.4. Clipping provides complimentary cumulative effect of improving the quality of the distribution function (CCDF) and decreased quality of Bit Error Rate (BER). Finally, the smaller the value of the clipping ratio CCDF quality improvement will be higher and the BER degradation will be even greater.